(untitled) (Journal of Environmental Bioremediation and Toxicology, 2025)
This study investigated the phytoremediation efficiency of the plants Aloe barbadensis and Ricinus communis for the removal of arsenic (As) from contaminated soil. The experiment was conducted in a Completely Randomized Block Design (CRBD) to assess arsenic (As) uptake across plant parts and residual soil after four weeks of exposure to 200, 600, and 1000 mg As treatments. Atomic Absorption Spectrophotometry (AAS) was utilized to determine Arsenic accumulation and concentration. Both plant species exhibited dose-dependent accumulation, with A. barbadensis showing significantly higher root uptake (606.51 ± 1.88 mg kg⁻¹ at 1000 mg) compared to R. communis (393.46 ± 3.09 mg kg⁻¹). Total arsenic removal efficiencies reached 89.7% for A. barbadensis and 76.5% for R. communis, confirming arsenic removal from contaminated soils. However, the uptake efficiency was found to decline slightly at higher As concentrations. Statistical analysis revealed significant differences (p < 0.001) between species, tissues, and treatment levels. The findings indicated that A. barbadensis is an excellent phytostabilizer of arsenic and recommend its use for eco-friendly remediation of As-polluted soils.